An update on the diagnosis and treatment of adult Moyamoya disease taking into consideration controversial issues. (May 2014) - Kim, Jeong Eun; Jeon, Jin Sue
<x content-type="archive" xml:space="preserve">Abstract</x> Moyamoya disease (MMD) is characterized by a chronic progressive steno-occlusive disease at the distal portion of the internal carotid artery (ICA) with abnormal Moyamoya vessel (MMV) development without associated diseases. Recent advances in radiologic tests have increased the number of MMD patients. Beyond detection improvement by magnetic resonance angiography (MRA) or cerebral angiography, predicting factors for disease severity, future hemorrhage, clinical outcome, post-op complications, and technical advances in assessing cerebral hemodynamics have been increasingly reported. Although treatment of pediatric MMD is well established, controversy remains over the treatment in adult patients. In particular, there are debates over the disease entity of adult MMD, contralateral progression in adult unilateral MMD, treatment strategy for asymptomatic adult MMD, and the association of MMD with thyroid disease. The purpose of this review is to provide an update on the diagnosis and treatment of adult MMD while addressing controversial issues.